Bridging the Gap Between the Classroom and the Clerkship: A Clinical Reasoning Curriculum for Third-Year Medical Students - Nicholas S. Duca; Susan Glod (Association of American Medical Colleges, 2019)
Introduction Clinical reasoning is the complex cognitive process that drives the diagnosis of disease and treatment of patients. There is a national call for medical educators to develop clinical reasoning curricula in undergraduate medical education. To address this need, we developed a longitudinal clinical reasoning curriculum for internal medicine clerkship students. Methods We delivered six 1-hour sessions to approximately 40 students over the 15-week combined medicine-surgery clerkship at Penn State College of Medicine. We developed the content using previous work in clinical reasoning, including the American College of Physicians' Teaching Medicine Series book Teaching Clinical Reasoning. Students applied a clinical reasoning diagnostic framework to written cases during each workshop. Each session followed a scaffold approach and built upon previously learned clinical reasoning skills. We administered a pre- and postsurvey to assess students' baseline knowledge of clinical reasoning concepts and perceived confidence in performing clinical reasoning skills. Students also provided open-ended responses regarding the effectiveness of the curriculum. Results The curriculum was well received by students and led to increased perceived knowledge of clinical reasoning concepts and increased confidence in applying clinical reasoning skills. Students commented on the usefulness of practicing clinical reasoning in a controlled environment while utilizing a framework that could be deliberately applied to patient care. Discussion The longitudinal clinical reasoning curriculum was effective in reinforcing key concepts of clinical reasoning and allowed for deliberate practice in a controlled environment. The curriculum is generalizable to students in both the preclinical and clinical years.